2021
DOI: 10.1111/cla.12462
|View full text |Cite
|
Sign up to set email alerts
|

Historical biogeography of Tetrastigma (Vitaceae): Insights into floristic exchange patterns between Asia and Australia

Abstract: Biodiversity exchanges across the Malesian region, linking the distinct biotas of Asia and Australia, have long attracted the curiosity of biologists. Tetrastigma (Vitaceae) has a wide distribution in Asia through the Sunda archipelago to Australia and provides a good case to elucidate floristic exchange between Asia and Australia. Tetrastigma species have fleshy fruits that are consumed by birds, representing a lineage with a predictable dispersal across island chains. We herein estimate the divergence times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
(105 reference statements)
1
8
0
Order By: Relevance
“…(2015) indicated that migrations of angiosperm clades from Sunda to Sahul predominated over the reverse direction 2.4 times. Our results are consistent with those reported in previous studies on plant groups that migrated from Asia to Australasia (e.g., Grudinski et al., 2014 ; Crayn et al., 2015 ; Peng et al., 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…(2015) indicated that migrations of angiosperm clades from Sunda to Sahul predominated over the reverse direction 2.4 times. Our results are consistent with those reported in previous studies on plant groups that migrated from Asia to Australasia (e.g., Grudinski et al., 2014 ; Crayn et al., 2015 ; Peng et al., 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Most of our sampled lineages (27/29) are components of tropical forests, and there is no evidence of habitat shift during their evolutionary histories. Studies on Tetrastigma have found the establishment of suitable habitats facilitated the southward expansion of species, and their restricted distribution in wet forests of Australia likely reflects the low adaptability of Tetrastigma to new environmental conditions outside their ancestral niche ( Yap et al., 2018 ; Peng et al., 2021 ). In addition, the limited northward dispersal of Tetrastigma might be attributed to competition pressure in the already established northern flora ( Peng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Planch. (Vitaceae) comprises about 120 dioecious species of mostly woody lianas, with a wide distribution throughout subtropical and tropical Asia, extending to Australia (Peng et al., 2021; Wen et al., 2018). As the sole perennial herbaceous species of this genus, Tetrastigma hemsleyanum Diels et Gilg (2 n = 2 x = 52) is widespread throughout subtropical China (Wang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%